Assessment on thermal behavior of municipal sewage sludge thin-layer during hot air forced convective drying. (5th March 2016) - Huang, Y.W.; Chen, M.Q.; Jia, L.
Highlights: Thermal behavior of sewage sludge thin layer in hot air drying was revealed. Effects of hot air temperature and speed on temperature of thin layer were gained. Average surface heat and mass transfer coefficients were determined. Dimensionless heat transfer correlation in 1st falling rate stage was developed. Abstract: Thermal behavior on the municipal sewage sludge thin-layer in a bench-scale hot air forced convective dryer was investigated at a hot air temperature range of 100–160 °C and three hot air speeds (0.6, 1.4, and 2.0 m s −1 ). The drying process presented four distinctive stages: a warm up stage, a constant rate stage, the first and the second falling rate stages. The temperature of the thin-layer increased rapidly in the first falling rate stage, whereas it rose slightly in the second falling rate stage. The average surface heat transfer coefficients in the first falling rate stage were about 3 times more than that in the second falling rate stage. The average surface heat and mass transfer coefficients at 0.6 m s −1 hot air speed increased by about 39% and 91% with an increase of the hot air temperature from 100 to 160 °C. The dimensionless surface heat transfer correlation of the sewage sludge thin-layer was obtained for the first falling rate stage. The model could fit the experimental data within ±25% deviation.